DENGUE FEVER AND LABORATORY TESTING AND MEDICATION - Adel Musaad Alabdulmunim , Majed Hamdan Alanazi, Ahmed Dhahi Alenezi; Zahiyah Salem Hamdan alenezi (Chelonian Research Foundation, 2023)
Dengue fever is a significant public health issue in many regions of the world, causing a substantial burden on healthcare systems and economies. Laboratory testing plays a crucial role in the diagnosis of dengue fever, allowing for early identification and appropriate treatment. This essay explores the laboratory testing methods used in the diagnosis of dengue fever, as well as the medications commonly prescribed for its treatment. The methodology involves a review of current literature on dengue fever testing and medication. The results indicate that laboratory testing for dengue fever includes various methods such as PCR, NS1 antigen testing, and antibody tests. Treatment for dengue fever primarily focuses on supportive care, with fluid management being the cornerstone of treatment. The discussion delves into the challenges of diagnosing dengue fever and the importance of early detection in reducing complications. In conclusion, laboratory testing is essential in the management of dengue fever, and prompt diagnosis and appropriate treatment are critical in improving patient outcomes. Keywords: Dengue fever, laboratory testing, medication, diagnosis, treatment